2013
DOI: 10.1002/phar.1369
|View full text |Cite
|
Sign up to set email alerts
|

Acute Decompensated Heart Failure: Evolving Literature and Implications for Future Practice

Abstract: Acute decompensated heart failure (ADHF) is associated with substantial morbidity and mortality, and represents a considerable financial burden to society. Historically, few prospective, randomized, double-blinded trials have investigated the optimal management of ADHF, and most guideline recommendations are based primarily on expert opinion. However, in the last decade, a considerable amount of research has added to the understanding of the management of ADHF in both patients with fluid overload and low cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…These patients typically exhibit reduced cardiac reserve and are therefore vulnerable to decompensated AHF after acute stimulus 5. There is clinical evidence that the hemodynamic characteristics of AHF patients may be somewhat different from those with chronic heart failure 6.…”
Section: Introductionmentioning
confidence: 99%
“…These patients typically exhibit reduced cardiac reserve and are therefore vulnerable to decompensated AHF after acute stimulus 5. There is clinical evidence that the hemodynamic characteristics of AHF patients may be somewhat different from those with chronic heart failure 6.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of ADHF cases are complicated by elevated blood pressure, which may cause overloading of the heart and increased peripheral vascular resistance, thereby exacerbating the hemodynamic conditions ( 6 , 20 ). Vasodilators have been recommended as the first-line medication for patients with ADHF, which may be due to their ability to stabilize the hemodynamic status ( 4 , 9 ). The present study demonstrated that intravenous administration of urapidil and nitroglycerin conferred similar blood pressure-lowering effects in elderly patients with ADHF and hypertension, without having adverse effects on HR.…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant improvements in the diagnosis and treatment of heart failure (HF), the mortality and morbidity rates for patients with HF remain high ( 1 3 ). For patients with hypertension, in particular elderly patients, the long-term overload of the heart caused by increased afterload, as well as reduced preservation of cardiac function, increases their susceptibility to cardiac insufficiency, which manifests clinically as acute decompensated HF (ADHF) ( 4 ). The hemodynamic characteristics of patients with ADHF have been shown to be different from those of patients with chronic HF (CHF) ( 5 ).…”
Section: Introductionmentioning
confidence: 99%